Pedagogical and Clinical Approaches to Musicians’ Health: A dialogue across disciplines (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
This dialogue derives from a shared interest in the well-being of musicians and the advancement of the field of the performing arts. These concerns address the age-old dualities between mind and body, theory and practice, as well as the neglect of performers' affective and embodied experiences in pedagogy and healthcare.
Keywords: Music; health and well-being; emotional literacy; embodiment; creativity; education; psychology; phenomenology